2000
DOI: 10.1159/000025250
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function in Platelet Concentrates during Storage: Comparison of Two Blood Cell Separators

Abstract: Background: In a controlled, randomized, prospective, open, comparative study we evaluated the platelet function of 112 platelet concentrates (PC) prepared by apheresis during 5-day storage. Material and Methods: In one group, 56 PC were prepared by blood cell separator CS-3000 Plus (Baxter GmbH) and the collecting chamber PLT 30 with the Omnix system; in the second group, 56 PC were prepared by blood cell separator AS-104 (Fresenius AG). In order to assess the platelet function of PC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(26 reference statements)
0
5
0
3
Order By: Relevance
“…In conclusion, the study showed that an increasing number of platelets became activated during 24 h of storage and could no longer be induced to adhere or to aggregate appropriately [30]. At the same time, platelets dissolved and cell debris as well as microparticles occurred.…”
Section: Resultsmentioning
confidence: 81%
“…In conclusion, the study showed that an increasing number of platelets became activated during 24 h of storage and could no longer be induced to adhere or to aggregate appropriately [30]. At the same time, platelets dissolved and cell debris as well as microparticles occurred.…”
Section: Resultsmentioning
confidence: 81%
“…The contents of the syringe are well mixed during the blood withdrawal. [2][3][4][5][6] Within 30 minutes after blood sampling and careful homogenization, the mixture is assayed in an automatic hematology analyzer (Sysmex M-2000, Digitana AG, Hamburg, Germany). The stability of test samples is at least 2 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The stability of test samples is at least 2 hours. [4][5][6] The number of platelets in the EDTA-formalin sample is reduced by the number of platelets forming as platelet aggregates. Using the ratio of the red blood cell count of both samples (EDTA / EDTA-formalin) the measurement error arising from the blood sampling can be corrected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of blood from animal species (e.g., pig and sheep) instead of human blood has to be avoided, particularly in view of the species‐dependent platelet function . In blood products, such as frozen plasma or platelet concentrates, proteins (e.g., factors V and VIII, or cytokines) and cells (e.g., platelet adhesion and aggregation) undergo functional alterations due to the processing (e.g., cooling and freezing), storage (e.g., storage lesion of cells), and stabilization . Thus, the use of blood products should be avoided since it very likely lead to an underestimation of the thrombogenicity of the tested materials.…”
Section: Prerequisites For a Reproducible In Vitro Testingmentioning
confidence: 99%